Observations on the courtship behavior and nesting in Phyllomedusa venusta (Anura: Phyllomedusidae) from a seasonally dry forest in Colombia - Mendoza-Roldán, Juan Salvador (Phyllomedusa: Journal of Herpetology, 2017)
I investigated the reproductive behavior of the poorly known leaf frog Phyllomedusa venusta. Courtship, amplexus, and nesting were observed during the rainy season in an ephemeral pool surrounded by forest. Based on the behavior of a single, amplectant pair, it seems likely that physical stimulation may play a role in courtship in this leaf frog that shows little vocalization. A second amplectant pair formed a nest, with leaves surrounding the clutch in a funnel. Both ends of the nest were plugged with empty jelly egg capsules, which also were dispersed throughout the egg mass. A separate spawn was collected, containing 390 viable eggs. By wrapping eggs in leaves, and depositing water in empty egg capsules in the egg mass and jelly plugs, the frogs doubtless protect developing embryos from desiccation, an important adaptation for leaf-nesting among phyllomedusids.